Ketogenic Diet in the Treatment of Super-Refractory Status Epilepticus at a Pediatric Intensive Care Unit: A Single-Center Experience - Breu, Markus; Häfele, Chiara; Glatter, Sarah; Trimmel-Schwahofer, Petra; Golej, Johann; Male, Christoph; Feucht, Martha; Dressler, Anastasia (Frontiers in Neurology, 2021)
OBJECTIVE: To evaluate the use of the ketogenic diet (KD) for treatment of super-refractory status epilepticus (SRSE) at a pediatric intensive care unit (PICU) DESIGN: A retrospective analysis of all pediatric patients treated for SRSE with the KD at our center was performed using patient data from our prospective longitudinal KD database. SETTING: SRSE is defined as refractory SE that continues or recurs 24 hours or more after initiation of anesthetic drugs. We describe the clinical and EEG findings of all children treated with KD at our pediatric intensive care unit (PICU). The KD was administered as add-on after failure of standard treatment. Response was defined as electroencephalographic (EEG) seizure resolution (absence of seizures and suppression-burst ratio ≥50%) PATIENTS: 8 consecutive SRSE patients (4 females) treated with KD were included. Median age at onset of SRSE was 13.6 months (IQR 0.9-105), median age at KD initiation was 13.7 months (IQR 1.9 months – 8.9 years). Etiology was known in 6/8 (75%): genetic in 4 (50%), structural in 1 (12.5%), and autoimmune/inflammatory in 1 (12.5%). RESULTS: Time from onset of SRSE to initiation of KD was median 6 days (IQR 1.3-9). Time until clini-cally relevant ketosis (beta-hydroxybutyrate (BHB) >2mmol/l in serum) was median 68.0 hours (IQR 27.3-220.5). Higher ketosis was achieved when a higher proportion of enteral feeds was possible. Four (50%) patients responded to KD treatment within 7 days. During follow-up (median 4.2 months, IQR 1.6-12.3), 5/8 patients – 3 of them responders -died within 3-12 months after SRSE. CONCLUSIONS: In 8 patients with SRSE due to severe etiologies including Alpers syndrome, we report an initial 50% response to KD. KD was used early in SRSE and sufficient levels of ketosis were reached early in most patients. Higher ketosis was achieved with combined enteral and parenteral feedings